2018
DOI: 10.1016/j.trf.2018.06.024
|View full text |Cite
|
Sign up to set email alerts
|

User acceptance of automated shuttles in Berlin-Schöneberg: A questionnaire study

Abstract: Automated shuttles are now in a prototyping phase in several research projects. However, there is still a paucity of knowledge on the acceptance of these shuttles. This paper presents the results of a questionnaire study among individuals (n = 384) who physically experienced an automated shuttle on an office campus in Berlin-Schöneberg. The findings indicate that the respondents were positive towards automated shuttles and could envision their use as feeders to public transport systems, in both urban and rural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
126
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 211 publications
(136 citation statements)
references
References 26 publications
(30 reference statements)
7
126
3
Order By: Relevance
“…The perceived enjoyment of taking a ride in driverless vehicles was also rated positively by respondents (M = 4.90/6, Q37). This corresponds with Nordhoff et al [20], who found that respondents strongly agreed with the statement that the driverless vehicle was fun and enjoyable after having taken a ride in the vehicle (M = 5.40/6). Our respondents gave the highest rating (M = 5.18/6, Q36) to being able to take over control from a driverless vehicle by a button inside the vehicle to stop it, which indicates that participants want to be able to retain some degree of control over the driverless vehicle.…”
Section: Main Results At the Individual Levelsupporting
confidence: 86%
See 2 more Smart Citations
“…The perceived enjoyment of taking a ride in driverless vehicles was also rated positively by respondents (M = 4.90/6, Q37). This corresponds with Nordhoff et al [20], who found that respondents strongly agreed with the statement that the driverless vehicle was fun and enjoyable after having taken a ride in the vehicle (M = 5.40/6). Our respondents gave the highest rating (M = 5.18/6, Q36) to being able to take over control from a driverless vehicle by a button inside the vehicle to stop it, which indicates that participants want to be able to retain some degree of control over the driverless vehicle.…”
Section: Main Results At the Individual Levelsupporting
confidence: 86%
“…In contrast, one online survey study in their review [19] found that people aged 36 to 65 had a more positive attitude and a stronger intention to use automated vehicles than people aged 18 to 35. In Nordhoff et al [20], older people were more likely to intend to use driverless vehicles and were more positive towards the vehicle characteristics, but gave lower ratings to the effectiveness of the vehicle compared to their existing travel mode.…”
Section: Individual Predictors Of Acceptancementioning
confidence: 98%
See 1 more Smart Citation
“…The reactions to service based on AVs were positive as part of the project CityMobil2 [14]. The users could envision it as a feeder mobility service to public transportation [15].…”
Section: State Of the Artmentioning
confidence: 99%
“…Various research projects are pursuing the development and introduction of automated shuttles (e.g., Transport Systems Catapult, 2016;WEpods, 2017). The public's acceptance of automated vehicles has been investigated in a number of questionnaire studies (e.g., Eden, Nanchen, Ramseyer, & Evéquoz, 2017a;Nordhoff, De Winter, Kyriakidis, Van Arem, & Happee, 2018;Nordhoff, De Winter, Madigan, et al, 2018;Vöge & McDonald, 2003). Most studies involved respondents who were asked to imagine automated vehicles, while some studies asked respondents to rate actual automated vehicles after physically experiencing them.…”
Section: Introductionmentioning
confidence: 99%